Penerapan K-Nearest Neighbor Untuk Klasifikasi Tingkat Kelulusan Pada Siswa Sma Negeri 11 Kota Bengkulu - Dofey Supriadi; Yupianti Yupianti; Eko Suryana (Jurnal Media Infotama, 2023)
Abstract-Bengkulu City 11 Public High School is one of the State Senior High Schools in Bengkulu City. The student's pass rate refers to the final score obtained for each subject, then calculates the average score to get the student's pass rating. So far, the school does not have an application that can help provide a predictive picture of student graduation. Where this needs to be done in order to evaluate the teaching and learning system so that students are able to face the final exam given The K-Nearest Neighbor application for classifying graduation rates for students at State Senior High School 11 Bengkulu City can help provide an informational description of the graduation rate for students at State High School 11 Bengkulu City and can provide information on the results of the classification results for high school graduation rates. State 11 City of Bengkulu. Based on the results of the tests that have been carried out, the functional application of the graduation rate classification of students at the Bengkulu City 11 State Senior High School is going well as expected.